The contribution of rohis on religious character education in senior high school 1 parakan - Veni Nurhayati; Sigit Tri Utomo; Nur Alfi Mu’anayah; Jundil Islam Muhammad Muslikhin (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study looks at the contribution of Rohani Islam (Rohis) in the formation of religious character education through its various activity programs. Seeing the widespread phenomenon such as juvenile delinquency, character education is the solution to these problems. The purpose of this study is to describe Rohis' contribution in the formation of religious character education and supporting and inhibiting factors in the formation of religious character education at SMA Negeri 1 Parakan. This research approach uses a narrative approach. This type of research uses field research with qualitative research methods. Primary data sources were obtained from interviews with Rohis members, chairmen and coaches, educators, principals and waka students of SMA Negeri 1 Parakan and secondary data sources from books related to Rohis extracurricular activities and documentation of Rohis activities. Data collection techniques by observation, interviews, and documentation studies. This research data analysis technique with data reduction steps, data presentation, followed by drawing conclusions. Triangulation of this research data using triangulation techniques and sources. This research approach uses a narrative approach. This type of research uses field research with qualitative research methods. Primary data sources were obtained from interviews with Rohis members, chairmen and coaches, educators, principals and waka students of SMA Negeri 1 Parakan and secondary data sources from books related to Rohis extracurricular activities and documentation of Rohis activities. Data collection techniques by observation, interviews, and documentation studies. This research data analysis technique with data reduction steps, data presentation, followed by drawing conclusions. Triangulation of this research data using triangulation techniques and sources. The results showed that Rohis' contribution in shaping character education was integrated through comprehension activities, through habituation, and through the example given by coaches and educators to students. The supporting factors of Rohis in the formation of religious character education are support from the school, the enthusiasm of students in participating in activities, and adequate infrastructure, while the inhibiting factor is limited activity time.